2005
DOI: 10.1002/adfm.200500218
|View full text |Cite
|
Sign up to set email alerts
|

Macroporous Silicon Microcavities for Macromolecule Detection

Abstract: Macroporous silicon microcavities for detection of large biological molecules have been fabricated from highly doped n‐type silicon. Well‐defined controllable pore sizes up to 120 nm have been obtained by systematically optimizing the etching parameters. The dependence of the sensor sensitivity on pore size is discussed. Excellent infiltration inside these macroporous silicon microcavities is demonstrated using 60 nm diameter latex spheres and rabbit IgG (150 kDa; 1Da = 1 g mol–1). The sensing performance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
205
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(209 citation statements)
references
References 42 publications
(43 reference statements)
4
205
0
Order By: Relevance
“…A decrease in the ability to bind streptavidin was observed for surface concentrations of biotin above 50% and was attributed to steric crowding within the biotin layer. 19 In this study we leverage the optical response of the PSi sensor to directly investigate each layer of a sandwich assay which attaches a biotinylated receptor antibody to the biotin/SA linking chemistry in order to optimize target detection. Taking a "bottom-up" approach we observe strong steric crowding effects in each layer of the receptor linking stack (biotin/SA/receptor) and identify distinct differences when compared to results reported on planar gold surfaces.…”
Section: (Equation 1)mentioning
confidence: 99%
See 2 more Smart Citations
“…A decrease in the ability to bind streptavidin was observed for surface concentrations of biotin above 50% and was attributed to steric crowding within the biotin layer. 19 In this study we leverage the optical response of the PSi sensor to directly investigate each layer of a sandwich assay which attaches a biotinylated receptor antibody to the biotin/SA linking chemistry in order to optimize target detection. Taking a "bottom-up" approach we observe strong steric crowding effects in each layer of the receptor linking stack (biotin/SA/receptor) and identify distinct differences when compared to results reported on planar gold surfaces.…”
Section: (Equation 1)mentioning
confidence: 99%
“…12 Recently, Ouyang et al 19 observed steric crowding when binding SA to biotin in a PSi optical sensor 13 , but the effect was not characterized in detail. In this study we characterize the effect of each layer in the sandwich assay on the immobilization of the subsequent layer with the goal of optimizing IgG target detection sensitivity.…”
Section: Optimization Of Linking Chemistry To Maximize Igg Target Detmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since a thin film is not a resonant structure, the sensitivity of the single layer PSi biosensor is limited as there is no sharp feature in the optical spectrum for which to accurately monitor small reflectance shifts. Multilayer PSi microcavities have also been used to detect various biomolecules [6] [7]. The drawback of these devices is their several micron thickness, which increases the infiltration time.…”
Section: Introductionmentioning
confidence: 99%
“…This principle is applied in porous biosensors [6]. If the pores are filled with an optically tunable medium, then the optical properties of the PSi sample also become tunable.…”
Section: Introductionmentioning
confidence: 99%